Design module for speech recognition graphical user interface browser to supports the web speech applications - Fadya A. Habeeb; Suaad M. Saber; Shaymaa Mohammed Abdulameer; Hassan Muwafaq Gheni; Ahmed Dheyaa Radhi (Institute of Advanced Engineering and Science, 2022)
The web speech API has made it possible to integrate audio data into web applications and make it a unique experience for all customers and users of modern applications. The website can only be accessed through devices equipped with a which stands for graphical user interface (GUI) and screen. For this to be done, there must be a physical attraction with such devices. This paper presents speech recognition using a web browser (SRWB) which permits browsing or surfing the internet with the use of a standard voice-only and vocal user interface (VUL) development. The SRWB system input from the users in form of vocal commands and covers these voice commands to HTTP requests. The SRWB system will send the voice commands to the web server for processing purposes and when the processing is done, the converted or translated HTTP response is outputted to the end-users in a voice format made audible with the attached loudspeakers. SAPI, developed by Microsoft, allows the use of SRWB in Windows applications. The algorithm is implemented by the system to achieve its goal for web content, classifying, analyzing, and sending important parts of web pages back to the end-user.